Choosing the Best Alternative to Run a Culinary Business Using Simple Multi Attribute Rating Technique: The Case of Demi Kamu Cafe - Aziziah, Syarifah Rena Iftitan; Novani, Santi (Journal of Business and Management, 2017)
AbstractThe growing trend of culinary business in Kediri area triggered one of its youth, Della, to create one, named Demi Kamu. In spite of the type of food sold, the price, the decoration, the location is an important aspect that can affect sales of a restaurant. According to Forbes, if someone’s thinking about opening a coffee shop or bistro, location is everything. This research was performed using qualitative method. According the in-depth interview by using root cause analysis with the owner, she already had three alternatives to establish the cafe, which are Ruko Mojoroto, Ruko Kawi, and Old House. This research evaluates all alternatives based on pre-determined attributes by using Simple Multi Attribute Rating Technique (SMART). If the decision maker’s extra value point < Rp41.906.846 then the decision maker should choose Ruko Mojoroto and if not then the decision maker should choose Old House. After some calculation, the result is Rp6.161.971/point. The owner then should choose Ruko Mojoroto as the best alternative. Lesson learned from this study was that it was true location is the most important thing to establish a restaurant. The use of SMART analysis was really effective in choosing on of some alternatives given. Keywords: SMART, Root cause analysis, Fishbone diagram, Decision analysis, Culinary business